Clinicomicrobiological profile of infective endocarditis in a tertiary care center of Nepal - Ghimire, M; Karki, P; Khanal, B; Acharya, P; Sharma, SK; Pahari, Bishnu (Journal of College of Medical Sciences-Nepal, 2013)
Background Infective endocarditis is a common problem and data regarding its clinical and microbiological pattern from developing countries are sparse. We studied clinical features and the microbiological pathogens in patients with Infective Endocarditis in our Hospital. Objective To study the clinical profile and microbiological pathogens involved in patients with Infective Endocarditis, admitted under Department of Internal Medicine of B.P Koirala Institute of Health Sciences. Materials and methods A total of 54 patients with history of fever and underlying heart disease were studied. It was a hospital based cross sectional descriptive study done in patients with infective endocarditis presented to us from March 2007 to February 2008 in B.P Koirala Institute of Health Sciences. Results Out of 54 patients, 11 (20.4%) had Dukes definite IE. The male: female ratio was 1.2:1. The mean age of the study group was 27.3 years (range=16-55). In IE group, fever was present in 100% cases (n=11) as it was the inclusion criteria of the study, followed by SOB 81.8% (n=9). History of antibiotic therapy prior to the presentation was present in 36.7 % (n=4) patients. Pallor was the most common sign 63.6% (n=7). Splenomegaly was seen in 18.2% (n=2). Anaemia (Hb<10gm %) in 36.4% (n=4) and microscopic haematuria in 72.3% (n=8) cases. Blood culture positivity was seen in 36.4 %. The most common pathogens were Staphylococcus aureus in 27.3% (n=3) and Acinetobacter species in 9.1% (n=1). Conclusion In our study we found that the clinical spectrum of IE was different from the west in that the majority of patients being young in our study. However, RHD still is the commonest underlying heart disease and Staphylococcus aureus being the commonest isolate. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-4, 34-41 DOI: http://dx.doi.org/10.3126/jcmsn.v8i4.8698